Fracture toughness testing of brittle materials using semi-circular bend (SCB) specimen - Kuruppu, Mahinda; Chong, K. (Elsevier, 2012)
The semi-circular bend (SCB) specimen was suggested in 1984 for testing mode I fracture toughness of rock and other geo or brittle materials. Since then SCB has been used worldwide, extended and improved for many other applications by various researchers. Formulations for mode I and mixed mode fracture of this specimen proposed by a number of researchers are presented. Methods to determine fracture toughness using both straight notched and chevron-notched specimens have been proposed although the general consensus is that a specimen having a sharp straight notch should yield accurate fracture toughness. Other applications of SCB specimen include testing of rock subjected to in situ conditions such as elevated temperature, confining pressure and pore water pressure. Furthermore it has been proven that it is a suitable specimen to test fracture toughness of rock at very high strain rates. Areas requiring further research to improve the accuracy of formulations are identified.